The Relation Between Biosecurity Measures and the Level of Staphylococcus aureus Contamination in Poultry Farms in Northern Iraq - R.F. Miro; Dh. M. Jwher (Journal of Applied Veterinary Sciences)
Despite receiving great attention to the poultry industry in Iraq, it is still affected by various problems that have led to great economic losses. Including Staphylococcus aureus, which causes invasive diseases such as arthritis and septicemia, as well as food poisoning in humans. This study aimed to assess the levels of biosecurity measures in poultry farms by evaluating the prevalence of Staphylococcus aureus contamination. in broiler farms located in different regions of Duhok, Nineveh and Erbil governorates, Iraq. A total of two hundred and thirty-four samples were collected fromTwenty-six poultry farms. The samples included swabs from chickens (skin swab), workers' hands, ventilators, feeders, drinking water, chicken feed, bedding, soil and grass (26 samples each); furthermore, the biosecurity levels in the investigated broiler farms were assessed via response to a descriptive questionnaire during the period from September 2024 to December 2024. The samples were subjected to biochemical and molecular tests, and the questionnaire data were statistically analyzed. Staphylococcus aureus was found in 43.16% (101 out of 234) of the samples. The highest isolation rate was from workers' hands, chicken (53.85%), while the lowest was from feeder and water (34.61%). According to this study, there were notable differences in the investigated farms’ biosecurity levels with an inverse relation to the occurrence of S. aureus. The lack of supporting evidence for the effectiveness of biosecurity measures to reduce the introduction and transmission of S. aureus in poultry farms in northern Iraq is a matter of concern and requires further studies on the sources of contamination and the mechanism of its spread and conducting sensitivity tests at regular intervals to determine the development of resistance to the antibiotics used.